Penyelenggaraan Pastoral Konseling Kepada Pemuda Korban Penyalahgunaan Narkoba dalam Meningkatkan Makna Hidup dan Menurunkan Stres (Jurnal Pendidikan Agama dan Teologi, 2024)
Drugs can penetrate all levels of society that do not recognize boundaries of status, age or gender. Drugs have become a part of culture in every country that has not yet eradicated them optimally. In the Indonesian context, the widespread use of illegal drugs among youth is of particular note, because they are human resources for building the nation. In fact, most people start using drugs at a young age. In aspects of life, it seems as if drugs have become a lifestyle for young people. For example, juvenile delinquency - such as free sex, drunkenness which occurs as a result of drug use. Victims of drug abuse are people who are dependent. Dependence is usually motivated by a lack of meaning in life and high levels of stress experienced by drug users. Pastoral counseling services are one of the therapies for their recovery in addition to medical, psychiatric and psychosocial therapy. Through pastoral counseling services, we will have a goal in writing articles, namely those that are characterized by increasing meaning in life and decreasing stress levels. It even brings them to know God better and to live with faith full of hope. This research uses a qualitative method with a literature review using a content analysis approach. And knowledge about how to overcome the meaning of life and stress using an Existential approach.